Anies Baswedan’s 2024 Candidacy Presidential Declaration: Norman Faircough Critical Discourse Analysis (Deklarasi Capres 2024 Anies Baswedan: Analisis Wacana Kritis Norman Fairclough) - Welsi Haslina; Afrini Rahmi; Ulfatmi Azlan (Jurnal Gramatika, 2023)
Discourse is a unit of language based on words used to communicate in social contexts. Therefore, it cannot be denied that language is an effective tool in all aspects of life, including on the political stage.This study aims to describe the linguistic strategy used by Anies Baswedan in representing himself as a 2024 presidential candidate. This research is descriptive qualitative research using the Norman Fairclough model of critical discourse analysis. The results showed that the linguistic strategy used by Anies Baswedan in his presidential deflation speech was according to the dimension of Fairclough's discourse. The text dimension in Anies Baswedan's speech shows Anies Bawedan's tendency to use diction with finer synonyms to describe criticism and use active voice to explain actions. The dimensions of discourse practice that Anies Baswedan utilizes are the electability of his supporting parties and his political career experience, as well as his vision and mission. Anies' declaration political speech was delivered when the integrity of the government was less stable so that the political discourse delivered was expected to be a solution to the problems faced by the community.